Why do users prefer the hedonic but choose the Utilitarian? Investigating user dilemma of hedonic–utilitarian choice. Issue 108 (December 2017) - Kakar, Adarsh kumar Saiindarlal
Highlights: Study investigates user dilemma in hedonic utilitarian choice of software features. Users favor utilitarian over hedonic features in explicit acquisition choice. However, their implicit acquisition choice is for the hedonic features. In forfeiture situation the choice is not dependent on hedonic and utilitarian characteristics. This dichotomy has interesting practical and theoretical implications. Abstract: Research studies have shown that although the hedonic product feature is more valued by users it is the utilitarian that is favored in acquisition choice situations. Further, the hedonic is more favored in forfeiture choice situations than the utilitarian. In this longitudinal study we examine this phenomenon with actual users of software. The results of the study show that as expected in acquisition situations users explicitly prefer the utilitarian although their implicit choice as reflected by the feature's impact on their satisfaction is for the hedonic. However, in forfeiture situations the explicit-implicit user preference is not based on hedonic–utilitarian considerations. The results also suggest the reason for this observed phenomenon. Unlike utilitarian features which consistently showed characteristics of Herzberg's hygiene factors in acquisition-forfeiture situations, hedonic features demonstrated characteristics of Herzberg's motivators only during acquisition, while demonstrating characteristics of hygiene factors during forfeiture. These findings offer interesting theoretical insights and have useful practical implications for product managers of software products.